Enhancing the sensitivity of interferometer sensing by slow light in photonic crystal waveguide - Wang, Qi; Zhang, Ya-nan; Han, Bo; Bai, Lu; Zhao, Yong (Photonics Letters of Poland, 2012)
A novel high sensitivity Mach-Zehnder interferometer (MZI) with slow light in photonic crystal waveguide (PCW) is proposed to enhance the sensitivity of fiber Brag grating (FBG) sensing system. The output intensity of MZI would be changed with the reflect center wavelength change of the FBG, which relates to the applied strain. By designing the PCW parameters, the measuring sensitivity of the applied strain can reach to 3.6 x 10-3rad/?? with a very high group index of 118. The active region is only 0.1 mm, which could be of great advantage in the use of the limited space. Full Text: PDF References Song, M. H., Yin, S. H., Ruffin, P. B., "Fiber Bragg grating strain sensor demodulation with quadrature sampling of a Mach-Zehnder interferometer", Applied Optics, 39(7), 1106-1111(2000). CrossRef Lee, S. M., Saini, S. S., Jeong, M. Y., "Simultaneous measurement of refractive index, temperature, and strain using etched-core fiber Bragg grating sensors", Photonics Technology Letters, 22(19): 1431-1433(2010). CrossRef Zhao, Y., Song, T. T., "Fiber Bragg grating current sensor based on birefringence effect", Microwave and Optical Technology Letters, 54(3): 822-826(2012). CrossRef Mihailov, S. J., "Fiber Bragg grating sensors for harsh environments", Sensors, 12(2), 1898-1918(2012). CrossRef Zhao, Y., Zhang, Y. N. and Wang, Q., "Research advances of photonic crystal gas and liquid sensors", Sensors and Actuators B: Chemical, 160(1), 1288-1297 (2011). CrossRef Chahal, M., Celler, G. K., Jaluria Y., "Thermo-optic characteristics and switching power limit of slow-light photonic crystal structures on a silicon-on-insulator platform", Optics Express, 20(4), 4225-4231(2012). CrossRef Baba, T., "Slow light in photonic crystals", Nature Photonics, 2(8), 465-473(2008). CrossRef Shen, C. Y., Zhong, C., "Novel temperature-insensitive fiber Bragg grating sensor for displacement measurement", Sensors and Actuators: A-Physical, 170(1-2), 51-54(2011). CrossRef http://ab-initio.mit.edu/wiki/index.php/MIT_Photonic_Bands. DirectLink Guo, S. P., Albin, S., "Simple plane wave implementation for photonic crystal calculations", Optical Express, 11(2), 167-175 (2003). CrossRef Petrov, A. Y., Eich, M., "Zero dispersion at small group velocities in photonic crystal waveguides", Applied Physics Letters, 85(21), 4866-4868(2004). CrossRef Li, J., T. White, P., Faolain, L. O., "Systematic design of flat band slow light in photonic crystal waveguides", Optical Express, 16(9), 6227-6232(2008). CrossRef Hao, R., Cassan, E., Roux, X. L., Gao, D., Khanh, V. D., Vivien, Laurent., Delphine, M. M., Zhang, X. X., "Improvement of delay-bandwidth product in photonic crystal slow-light waveguides", Optics Express, 18(16), 16309-16319 (2010). CrossRef Engelen, R. J. P., Sugimoto, Y., Watanabe, Y., "The effect of higher-order dispersion on slow light propagation in photonic crystal waveguides", Optics Express, 14(4), 1658-1672(2006). CrossRef